Uninterrupted embryonic growth leading to viviparous propagule formation in woody mangrove - Zhou, Xiaoxuan; Weng, Yulin; Su, Wenyue; Ye, Congting; Qu, Haidong; Li, Qingshun Quinn (Frontiers in Plant Science, 2023)
Vivipary is a rare sexual reproduction phenomenon where embryos germinate directly on the maternal plants. However, it is a common genetic event of woody mangroves in the Rhizophoraceae family. The ecological benefits of vivipary in mangroves include the nurturing of seedlings in harsh coastal and saline environments, but the genetic and molecular mechanisms of vivipary remain unclear. Here we investigate the viviparous embryo development and germination processes in mangrove Kandelia obovata by a transcriptomic approach. Many key biological pathways and functional genes were enriched in different tissues and stages, contributing to vivipary. Reduced production of abscisic acid set a non-dormant condition for the embryo to germinate directly. Genes involved in the metabolism of and response to other phytohormones (gibberellic acid, brassinosteroids, cytokinin, and auxin) are expressed precociously in the axis of non-vivipary stages, thus promoting the embryo to grow through the seed coat. Network analysis of these genes identified the central regulatory roles of LEC1 and FUS3, which maintain embryo identity in Arabidopsis. Moreover, photosynthesis related pathways were significantly up-regulated in viviparous embryos, and substance transporter genes were highly expressed in the seed coat, suggesting a partial self-provision and maternal nursing. We conclude that the viviparous phenomenon is a combinatorial result of precocious loss of dormancy and enhanced germination potential during viviparous seed development. These results shed light on the relationship between seed development and germination, where the continual growth of the embryo replaces a biphasic phenomenon until a mature propagule is established.